Textual Function of Discourse Markers: A Study of Gender Differences in Call Her Daddy "Ed Sheeran: You Either Love Me or Hate Me" on YouTube - Setyawan, Diky; Pradipta, Bramantya (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
Abstract This study investigates the textual functions of discourse markers (DMs) and explores gender-based differences in their usage in a real-life podcast conversation. The data source is the discourse markers from the utterances in the YouTube podcast Call Her Daddy, titled “Ed Sheeran: You Either Love Me or Hate Me,” featuring Alex Cooper as the host and Ed Sheeran as the guest. This research employs Brinton’s (1996) framework to categorize the textual functions of DMs and applies Deborah Tannen’s (1990) Difference Theory to examine gendered communication styles. Using a descriptive qualitative method, the study identifies 788 total discourse markers: 591 produced by the male speaker and 197 by the female speaker. The most dominant category of textual function was fillers, followed by information indicators and sequence/relevance markers. The findings reveal that Ed Sheeran, although male, frequently used fillers and repair markers typically associated with rapport-style communication. Meanwhile, Alex Cooper, despite using fewer DMs overall, relied heavily on topic switchers and turn-taking markers, aligning with her role as host. These patterns support Tannen’s theory that male speakers tend to emphasize information and logical structure (report talk), while female speakers focus on maintaining conversational flow and interpersonal rapport (rapport talk). The study highlights how discourse markers function not only as linguistic tools but also as reflections of gender identity, conversational role, and interactional purpose in digital media discourse. Keywords: discourse markers, gender differences, podcast, pragmatics, textual functions